School corporal punishment, family tension, and students' internalizing problems: Evidence from India. (February 2017) - Deb, Sibnath; Kumar, Aneesh; Holden, George W.; Simpson Rowe, Lorelei
There is considerable evidence that parental corporal punishment (CP) is positively associated with children's behavioral and mental health problems. However, there is very little evidence addressing whether CP perpetrated by teachers or school staff is similarly associated with problematic student functioning. To address this gap in the research literature, data were collected from students in a locale where school CP continues to be widely practiced. Participants were 519 adolescents attending public or private schools in Puducherry, a city in eastern India. Students completed surveys assessing school CP, internalizing problems, social support, and resilience. The results indicated that 62% of the students reported experiencing school CP in the past 12 months, with males and those attending public schools being significantly more likely to report school CP than females and those in private schools. Youth who reported school CP reported more anxiety and depression. That relation was more pronounced in youth who reported family tension. Social support and resilience did not moderate the relations. The findings add to the substantial evidence about negative associations regarding the use of CP but in a new venue—the school, and provide some evidence for the need to change how students are disciplined in schools in India and elsewhere.